The Relationship Between Spiritual Meaning of The Experience of Illness and The Use of Coping Strategies in People Living With HIV/AIDS - Rohman, Rohman; Nursalam, Nursalam; Sukartini, Tintin; Imansyah, Rahmat (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the relationship between the spiritual meaning of the experience of illness and coping strategies in people living with HIV/AIDS (PLWHA) at one hospital in Jakarta. The study used a cross-sectional design to PLWHA population with a sample size of 30 clients HIV positive, aged 28-29 years, who were willing to be respondents. The research instrument used questionnaires and data analysis with Chi- square test. The results of the study show that there is a relationship between the spiritual meaning of the experience of illness and coping strategies of PLWHA (p value 0.010). PLWHA who gave spiritual meaning to their illness experience in a positive way had 8 times more opportunities to use adaptive coping strategies compared to PLWHA who gave spiritual meaning to their illness experience in a negative way. These findings can provide evidence for nurses to facilitate and guide PLWHA in discovering the spiritual meaning of the experiences of illness and developing strategies for using positive coping in order to enhance their positive attitudes and behaviors.